A Socio-Cultural and Christian Educational Perspective on the Philosophy of Sõkhi Mate Moroi Aila in the Nias Ethnic Community-Indonesia - Amirrudin Zalukhu; Dirk Roy Kolibu (GoAcademica Research & Publishing, 2022)
Sõkhi mate moroi aila can be translated as better to die than to bear shame, is a local wisdom of the Nias community in the form of a philosophy of life that has influenced the formation of the identity of the Nias people who are willing to die in order to maintain the honour of themselves and their families. This philosophy has negative impacts, such as poverty, disharmony in the family, acts against the law but can also have a positive impact to raise the spirit and fighting power to achieve a better life. The philosophy of sõkhi mate moroi aila in this research is written based on the author's experiences and reflections as a person born, raised and nurtured in Nias culture as well as additional information from informants, selected books and journals. In this research, the author encourages the participation of the church and indigenous people to re-interpret the philosophy of sõkhi mate moroi aila from the perspective of the Christian faith that can bring peace to the common life of the Nias people.